Vesicular trafficking regulators are new players in breast cancer progression: Role of TOM1L1 in ERBB2-dependent invasion. (3rd July 2016) - Chevalier, Clément; Roche, Serge; Bénistant, Christine
ABSTRACT: ERBB2 (v-erb-b2 avian erythroblastic leukemia viral oncogene homolog 2) amplification is associated with invasive breast cancer. We discovered that TOM1L1 (target of myb1-like 1) and ERBB2 co-amplification defines a novel mechanism involved in breast cancer metastatic progression. Upregulation of the vesicular trafficking protein TOM1L1 enhances plasma membrane delivery of membrane-type 1 matrix metalloprotease (MT1-MMP) for efficient extracellular matrix degradation and tumor cell dissemination.